The Effectiveness of Cataract Surgery in Reducing Motor Vehicle Crashes: A Whole Population Study Using Linked Data - Meuleners, Lynn; Hendrie, Delia; Lee, Andy; Ng, Jonathon; Morlet, Nigel (Informa Health Care, 2012)
Purpose: To evaluate the effectiveness of first eye cataract surgery on drivers aged 60 years and over at a population level. Methods: A retrospective before and after comparison of all police reported crashes for patients who had undergone first eye cataract surgery using linked Western Australia data for the period 1997–2006. An economic analysis by the type of crash was performed on the cost savings from cataract surgery for this cohort. Results: Of the 27,827 patients who underwent cataract surgery in one eye only, 1715 patients were involved in 1762 police reported crash events, either 1 year before (n = 941 crashes) or 1 year after (n = 821 crashes) cataract surgery. Results from Poisson generalized estimating equations showed a significant reduction of 12.7% (P = 0.034) in all police reported crashes 1 year after cataract surgery. The corresponding cost savings amounted to $4.3 million. Conclusion: The findings are important for policy development to further improve driving outcomes among older drivers.